Outcomes of Surgical Treatment of Multiple Primary Colorectal and Prostate Cancer - I. S. Ignatov; V. V. Balaban; E. A. Bezrukov; A. V. Nikishina; M. He; P. V. Tsarkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2025)
Aim: to evaluate the outcomes of surgical treatment of patients with multiple primary cancer of the colon and prostate.Materials and methods. An observational retrospective study was conducted at the Clinic of Coloproctology and Minimally Invasive Surgery (I.M. Sechenov First Moscow State Medical University). A total of 3,640 protocols of the preoperative multidisciplinary team were studied from July 2018 to April 2024. The inclusion criterion was the diagnosis of multiple colorectal and prostate cancer. The medical documentation was collected in the database and analyzed.Results. The study included 39 patients: 24 patients with a metachronous variant of multiple primary cancer and 15 patients with a synchronous variant of the disease, which amounted to 1.1 % of all patients who underwent a preoperative consultation during the specified period. There were no significant differences in age, localization of tumors in the colon, methods of their treatment, access in surgical treatment of colorectal cancer, frequency of conversions and postoperative complications (p > 0.05). Prostate cancer was verified first in the group with the metachronous variant of multiple primary cancer significantly more often than in the group with the synchronous variant (95.8 % vs. 40.0 %, respectively; p < 0.001), and was also significantly more often treated surgically (75.0 % vs. 33.3 %; p = 0.018). Radical prostatectomy was performed via laparotomy significantly less frequently in the group with the synchronous variant than in the group with the metachronous cancer (0 % vs. 58.8 %; p = 0.046). No significant differences were found when comparing overall and recurrence-free survival in groups with metachronous and synchronous variants of multiple primary cancer.Conclusions. A clinician should be alert to multiple primary colorectal and prostate cancer. The first stage of therapy for the synchronous variant should be surgical treatment of colorectal cancer. The history of surgical treatment of one of the tumors is not a contraindication for the use of minimally invasive techniques, however, the choice of surgical approach should be individualized. The presence of prostate cancer may be another factor in favor of performing lateral lymph node dissection in patients with synchronous rectal cancer.